Environmentally sustainable implementations of two-dimensional nanomaterials - Shams, Mehnaz; Mansukhani, Nikhita; Hersam, Mark C.; Bouchard, Dermont; Chowdhury, Indranil (Frontiers in Chemistry, 2023)
Rapid advancement in nanotechnology has led to the development of a myriad of useful nanomaterials that have novel characteristics resulting from their small size and engineered properties. In particular, two-dimensional (2D) materials have become a major focus in material science and chemistry research worldwide with substantial efforts centered on their synthesis, property characterization, and technological, and environmental applications. Environmental applications of these nanomaterials include but are not limited to adsorbents for wastewater and drinking water treatment, membranes for desalination, and coating materials for filtration. However, it is also important to address the environmental interactions and implications of these nanomaterials in order to develop strategies that minimize their environmental and public health risks. Towards this end, this review covers the most recent literature on the environmental implementations of emerging 2D nanomaterials, thereby providing insights into the future of this fast-evolving field including strategies for ensuring sustainable development of 2D nanomaterials.